FEATURES OF COCHLEAR IMPLANTATION REHABILITATION - Rakhimova Khurshidakhon Sadikovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights current problems with the rehabilitation system for children with cochlear implants.